Proses Komunikasi Persuasif Pada Program Rehabilitasi Pecandu Narkoba Di BNNP Sulteng - Apriani, Karin; Ramah, Muchri; Rahmarini, Giska Mala; Khairil, Muhammad; Edwan; Utama, Roman Reski (Kinesik, 2026)
This study aims to describe and analyze the persuasive communication process carried out by counselors in the drug addict rehabilitation program at the National Narcotics Board of Central Sulawesi Province (BNNP Central Sulawesi). This research employs a qualitative approach with a descriptive research design. Data were collected through in-depth interviews, observation, and documentation, involving counselors and rehabilitation clients as informants. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The analysis of this study is based on Hafied Cangara’s Persuasive Communication Theory, which consists of the elements of communicator, message, media, communicant, and effects. The results of the study indicate that the persuasive communication process in the rehabilitation program is implemented in several stages, including screening, assessment, the formulation of therapy plans through individual counseling, outpatient rehabilitation, and post-rehabilitation